THE EFFECT OF MOTIVATION AND SUPERVISION ON THE PERFORMANCE OF PARKING ATTENDANTS IN KOTA JUANG DISTRICT - Junizal; Dinda Ghebrina Putri; Dedi Gunawan; Lukman Hakim (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of motivation and supervision on the performance of parking attendants in Kota Juang District, Bireuen Regency. The background of this research is the importance of improving the performance of parking attendants in providing orderly and secure parking services to the community. This research used a quantitative approach with a survey method. The population in this study consisted of all parking attendants operating in Kota Juang District, totaling 47 people. The sampling technique used was saturated sampling, where the entire population was used as the research sample. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS software. The results showed that motivation has a significant effect on the performance of parking attendants. Supervision also has a significant influence on their performance. Simultaneously, motivation and supervision significantly affect the performance of parking attendants. These findings indicate that increasing work motivation and strengthening supervision can improve the performance of parking attendants in Kota Juang District.